2019
DOI: 10.1186/s13046-019-1279-8
|View full text |Cite
|
Sign up to set email alerts
|

Mucin 17 inhibits the progression of human gastric cancer by limiting inflammatory responses through a MYH9-p53-RhoA regulatory feedback loop

Abstract: Background Mucins are key components of the mucosal barrier in the stomach that protects epithelia from carcinogenic effects of chronic inflammation. Analysis of The Cancer Genome Atlas database indicated that mucin-17 (MUC17) was more highly expressed in gastric cancer (GC) specimens, with favourable prognosis for patients. To explore the underlying mechanisms, we investigated the potential role of MUC17 in controlling chronic gastric inflammation. Methods We initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…Western blot analysis found that the MYH9 protein level was downregulated when overexpressing miR-124-3p and upregulated with the knockdown of miR-124-3p in microglia, which further confirmed that MYH9 was the target downstream gene of miR-124-3p. MYH9 has been demonstrated to show a positive role in cell inflammation [38,47]. Additionally, MYH9 has been identified to participate in BBB dysfunction in ischemic stroke and to mediate oxidative stress-induced neuronal apoptosis [48,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis found that the MYH9 protein level was downregulated when overexpressing miR-124-3p and upregulated with the knockdown of miR-124-3p in microglia, which further confirmed that MYH9 was the target downstream gene of miR-124-3p. MYH9 has been demonstrated to show a positive role in cell inflammation [38,47]. Additionally, MYH9 has been identified to participate in BBB dysfunction in ischemic stroke and to mediate oxidative stress-induced neuronal apoptosis [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that myosin heavy chain 9 (MYH9) may be the potential target related to inflammation attenuation (Additional file 2: Figure S1). Moreover, MYH9 has been demonstrated to show a positive role in endothelial cell inflammation [38]. To verify that MYH9 3′UTR is a direct target for miR-124-3p, wild-type (WT) and mutated (MUT) 3′-UTR sequences of MYH9 were constructed (Fig.…”
Section: Exosomal Mir-124-3p Regulates Myh9 By Directly Targeting 3′-utrmentioning
confidence: 99%
“…In their study, TTN was ranked as the single most prevalent gene among 518 protein kinase genes in 210 different human cancers associated with an extremely high density of cancer driver mutations [ 49 ]. On the other hand, although mucins are essential components of the mucous layer in extracellular space, mucins were also known to be involved in inflammation and cancer [ 50 ], while Mucin 17 was further found to inhibit the progression of human gastric cancer [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…None of the other three prognostic genes (MUC17, TAC4, OR8G5) have been reported in osteosarcoma, but MUC17 and TAC4 have been shown to play an important role in many cancers. MUC17 was more highly expressed in gastric cancer, and inhibited the progression of gastric cancer through a MYH9-p53-RhoA regulatory feedback loop to limited im ammatory responses [20]. TAC4 was a member of the tachykinin family of neurotransmitter-encoding genes.…”
Section: Discussionmentioning
confidence: 99%